2022
DOI: 10.1039/d2cp00522k
|View full text |Cite
|
Sign up to set email alerts
|

Electron–phonon coupling and superconductivity in a 2D Tl–Pb compound on Si(111)

Abstract: A first principles investigation of the electron–phonon interaction and phonon-mediated pairing strength in a Si(111) supported single-layer Tl–Pb compound reveals strong variations with electronic surface bands and binding energy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…In particular, it was found that a single-atom-thick metal film of Pb on Si(111) (so-called striped incommensurate (SIC) phase with 1.33 monolayers of Pb) possesses superconducting properties, , albeit with the critical temperature T c lower than that for the bulk lead, i.e., 1.1–1.83 K versus 7.2 K. It appears that the number of the examples for superconducting single-atom-layer films is very limited. Besides the above-mentioned Pb/Si(111) system, the other examples are a few Tl–Pb compounds on Si(111) and Ge(111) surfaces and a Sn layer on B-passivated Si(111) surface . In contrast, the list of the double-atom-layer superconductors was proved to be more extended.…”
mentioning
confidence: 99%
“…In particular, it was found that a single-atom-thick metal film of Pb on Si(111) (so-called striped incommensurate (SIC) phase with 1.33 monolayers of Pb) possesses superconducting properties, , albeit with the critical temperature T c lower than that for the bulk lead, i.e., 1.1–1.83 K versus 7.2 K. It appears that the number of the examples for superconducting single-atom-layer films is very limited. Besides the above-mentioned Pb/Si(111) system, the other examples are a few Tl–Pb compounds on Si(111) and Ge(111) surfaces and a Sn layer on B-passivated Si(111) surface . In contrast, the list of the double-atom-layer superconductors was proved to be more extended.…”
mentioning
confidence: 99%